Knoll : a modernist universe - Lutz, Brian (Rizzoli, 2010)
Since 1938, Knoll International has been at the forefront of 20th century furniture & interior design, commissioning such influential names as Ludwig Mies van der Rohe, Frank Gehry & Eero Saarinen to design pieces. This text looks at the history of Knoll, as well as providing a visual timeline of products, graphics & important landmarks.